Hanging Deaths at Tertiary Care Teaching Hospital - Shaik Khaja Moinuddin; V Chand Basha (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Hanging signifies an asphyxiation form which, by a noose or another constricting bandtightened by body weight, is secondary to compression or restriction of the neck structures. All hangings aresuicidal. Accidental and homicidal hangings are rare and uncommon.Objective: This research was performed on deaths attributed to neck strain related to hanging andstrangulation carried out for post-mortem analysis in the mortuary of Osmania General HospitalMethods: Detailed information regarding the deceased and the circumstances of the death were collectedfrom the police and relatives by a questionnaire. For certain situations, the detail was matched by an on-siteobservation or by photos of the incident location.Results: Knot was present in the right side of the neck in 97(48.5%) cases, over the left side of the neckin 62(31%) cases, and over the center of the occipital region in 41(20.5%) cases. In the present study, it isobserved that in 167(83.5%) cases, the level of ligature mark was above the thyroid cartilage, below thethyroid cartilage in 11(5.5%) cases, and overriding the thyroid cartilage in 22(11%) cases. parchmentizationwas present in 135(67.5%) cases and absent 65(32.5%) cases. The causes for these observations are theligature material type and the length of suspension which in the majority of cases are parchmentized. 169cases (84.5%) did not show any changes around the ligature mark, but in 31 cases (15.5%). Fracture of hyoidbone was seen in 3.5% of the cases and fracture of thyroid cartilage was seen in 4.5% of the casesConclusion: Our society has a great socio-economic burden due to the high incidence of suicidal hangingamong young adults particularly women. The private essence of hanging and convenient access to ligaturepoints and ligature supplies renders suicide avoidance challenging. Marital disappointment, organic diseaseissues, and dowry abuse are the primary reasons behind suicide hanging.